Elongation growth in leaf blades of Chloris gayana under saline conditions - Ortega, Leandro Ismael; Taleisnik, Edith (Elsevier, 2020)
In Chloris gayana, salinity-associated yield decreases are due mainly to leaf area reductions. To understand the physiological basis for such reduction, the effects of salinity were studied on the spatial and temporal distribution of extension in the intercalary meristem at the leaf base, and on hydraulic conductance in that zone. C. gayana plants were grown on sand irrigated with Hoagland solution with the addition of 0 or 200 mmol/L NaCl, and all measurements were performed on tiller leaf four. In salinised plants, that leaf was 20 percnt; shorter than in controls. Extension in the blade expansion zone was studied by pricking through the leaf sheaths and analysing the displacement of the pricks. In salt-treated plants, maximum growth rates were depressed by 53 percnt; and the growth zone was shorter by approximately 10 mm, nevertheless, extension proceeded for a longer period than in control plants. The analysis of specific leaf areas in the expansion zone suggests the rate of dry matter deposition was lowered by salinity and estimations of tissue displacement time within that zone suggest cell wall maturity was delayed. Hydraulic conductance was reduced by salinity and this may be the main cause for reduced growth under salinity in Chloris gayana.